DETERMINAN FERTILITAS DI INDONESIA - Syahmida Syahbuddin Arsyad; Septi Nurhayati (Research Centre for Population, Indonesian Institute of Sciences, 2016)
Fertility experiences stagnation during the last 10 years (2.6 children) and it did not reach the target of national medium-term development plan 2015 for 2.1 children. Meanwhile, the use of contraception increased less than one percent, and mortality rate of children under five years old only slightly declined. This might be because Population and Family Planning Program is not a priority. This paper aims to analyze direct and/or indirect factors that significantly cotribute to children born alive based on IDHS 2012. The IDHS 2012 data collect 45.607 women aged 15-49 years as sample units. Data was analyzed using descriptive statistics for univariate, bivariate (chi-square), and multivariate (multiple linear regression). Twenty-four variables have a significant relationship to the children born alive, eleven of the variables have strong effect to the children born alive. By taking into account control variables, the eleven variables contribute 66 per cent to children born alive. Child mortality is the most dominant variable that contributes to a children born alive This is in line with the theory of Alberto that said child mortality trigger to have more children. The results also explain that stagnation of fertility can not be separated from slow rate of mortality. Recommendations that developed by this analysis include the strengthening of communication, education, information, especially delayed age at first marriage, age at first birth and age at first sexual intercourse for young women, the lowest wealth quintile, low education throughÂ The Information Center of Adolescent Reproductive Health Councelling; b). Partnership with the Ministry of Health, especially strengthening education and information communication and quality of services mother and child care program concerning the high contribution of child mortality to the children ever born.